2016
DOI: 10.1111/1467-8268.12222
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Determinants of Unemployment in Nigeria: Do Resource Dependence and Financial Development Matter?

Abstract: The paper examines the determinants of unemployment in Nigeria from 1981 to 2013, using the error correction model (ECM), and with ordinary least squares (OLS) method for robustness check. Results from the short-run and long-run regressions show that resource dependence and growth in private credit/GDP by banks significantly worsen labour unemployment, suggesting likely effects of resource-curse, high cost of financial intermediation cum limited credit to the real economy. Real GDP per capita, FDI, trade openn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
(49 reference statements)
5
17
0
1
Order By: Relevance
“…Furthermore, some studies have also focused on investigating the determinants of unemployment within the context of the Nigerian economy for instance; Orji, Orji‐Anthony, and Okafor () investigated the unemployment inflation relationship in Nigeria and obtained a significant positive relationship among these two variables. In a different study, Ogbeide, Kanwanye, and Kadiri () while examining the determinants of unemployment in Nigeria applied the error correction term (ECM) approach and concluded that factors like resource dependence and high cost of financial intermediation exacerbate labor unemployment in the country. Considering the size of the Nigerian economy and the current unemployment challenges that are facing the nation despite being a potential trade hub among the sub‐Saharan African countries and in Africa at large, redressing the unemployment crisis within the trade discourse is particularly relevant.…”
Section: Literature Of Related Reviewmentioning
confidence: 99%
“…Furthermore, some studies have also focused on investigating the determinants of unemployment within the context of the Nigerian economy for instance; Orji, Orji‐Anthony, and Okafor () investigated the unemployment inflation relationship in Nigeria and obtained a significant positive relationship among these two variables. In a different study, Ogbeide, Kanwanye, and Kadiri () while examining the determinants of unemployment in Nigeria applied the error correction term (ECM) approach and concluded that factors like resource dependence and high cost of financial intermediation exacerbate labor unemployment in the country. Considering the size of the Nigerian economy and the current unemployment challenges that are facing the nation despite being a potential trade hub among the sub‐Saharan African countries and in Africa at large, redressing the unemployment crisis within the trade discourse is particularly relevant.…”
Section: Literature Of Related Reviewmentioning
confidence: 99%
“…The empirical methodology adopted in this study is similar to those of O'Nwachukwu (2017) and Ogbeide et al (2016). However, the contributions of this paper are different from those of these studies.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Fisman 2001;Sun et al 2011), it differs in the sense that it also involves recruiting people from target politicians' constituencies. In emerging countries such as Nigeria, unemployment is high (Ogbeide et al 2016) and its reduction is a constant promise politicians make on their campaign trails. Additionally, most Nigerian youth have very poor perceptions of blue-collar jobs (Dike 2010); hence, they prefer white-collar positions such as bank work, which is highly regarded and prestigious.…”
Section: [Respondent G1]mentioning
confidence: 99%